Visceral Organ Mass of Lambs Fed Four Roughage Diets - J. M. Abo Omar; K. Johnson; D. Johnson (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Twenty-eight lambs averaging 45 kg live weight were divided among four roughage dietary treatment : grass hay, corn silage, alfalfa and oat hay. The diets contained a minimum of 12% crude protein and provided 10% over the required energy for maintenance. Lambs were fed twice a day (0800 and 1700) for 28 days. Animals were weighed at 10-d intervals at 0700 prior to being fed that morning. At the end of the feeding period the lambs were slaughtered and the weights of fat-free gastrointestinal tract segments, their content and other organs were taken and expressed as g/kg of empty body weight (EBW) Sampled of the rumen and small intestine were separated into mucosa] and nonmucosal (serosal) fractions. No single forage diet consistently increased the weights of all visceral organs. However, lambs fed the 70% alfalfa hay has 12% heavier liver and lung weights (p < .05) compared to lambs receiving other treatments and 11% heavier small intestine weights compared to the oat and silage diets. The grass hay diets resulted in lambs with 55% heavier cecum dry weights (P < . 05) compared to other roughage sources . Lambs fed silage diets had 7% heavier rumen mucosa (wet and dry) weights . The roughage source had no effect on total rumen, omasum, large intestine and total tract weights or contents.